2005
DOI: 10.1007/s00380-004-0793-5
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of arterial stiffness by the antioxidant and anti-inflammatory effects of short-term statin therapy in patients with hypercholesterolemia

Abstract: The preventive effect of statins on coronary events is not only associated with the cholesterol-lowering effect of these drugs, but also various direct effects on the vascular wall, which include improvement of endothelial function, antioxidant activity, and anti-inflammatory activity. We investigated whether short-term statin therapy could improve arterial stiffness and assessed its mechanism of action in patients with hypercholesterolemia. We assessed arterial stiffness in 10 patients (mean age: 62.9 +/- 9.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 11 publications
0
21
0
4
Order By: Relevance
“…Furthermore, several reports indicate that statins improve oxidative stress 47,48) . So, statins might expect to improve CAVI although there are still no reports about the effects of statins on CAVI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several reports indicate that statins improve oxidative stress 47,48) . So, statins might expect to improve CAVI although there are still no reports about the effects of statins on CAVI.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, although similar studies using biological agents 25 in AS therapy failed to demonstrate significant improvement in arterial stiffness, there are reports indicating that therapy, life style changes and invasive procedures may successfully reduce arterial stiffness. 11,12 It has been shown that atorvastatin improves arterial stiffness through reduction of oxidative stress. 28 We previously revealed that anti-TNF-a therapy reduces oxidative stress in patients with AS.…”
Section: Discussionmentioning
confidence: 99%
“…10 Hence, PWV value has been used as an index for CV improvement following different treatment modalities in variety of conditions. 11,12 Our previous study revealed that PWV was higher in AS patients than in the control group. 8 Anti-TNF-a therapy has been associated with dramatic improvements in the clinical signs and symptoms of AS.…”
mentioning
confidence: 89%
“…в настоящее время достигнуты большие успехи по влиянию лекарственных препаратов различных групп на эластиче-ские свойства артерий, в том числе статинов [17][18][19][20]. однако продолжается поиск веществ, способных воздействовать на жесткость сосудистой стенки, что возможно, откроет новые перспективы в изучении механизмов ее увеличения.…”
Section: оригинальные статьи № 3/2014 остеопороз и остеопатииunclassified
“…в настоящее время по результатам некоторых исследо-ваний имеются данные об улучшении эластических свойств артериальной стенки на фоне терапии статинами у пациен-тов с гиперлипидемией [17][18][19][20]. в нашем исследовании не выявлено взаимосвязи динамики спвкф с изменениями со-держания липидов в сыворотке крови.…”
Section: результаты исследованияunclassified